Can physical activity counteract the negative effects of sedentary behavior on the physical and mental health of children and adolescents? A narrative review - Wang, Kun; Li, Yan; Liu, Hengxu; Zhang, Tingran; Luo, Jiong (Frontiers in Public Health, 2024)
Background The increase in sedentary behavior (SB) in children and adolescents is one of the major threats to global public health, and the relationship between physical activity (PA) and SB has always been a key topic. Methods The literature search was conducted through PubMed, Web of Science, CNKI, Wanfang, and Scopus, and 121 pieces of literature were included in this study after screening and evaluation. Results (1) SB caused by screen time such as mobile phones and TVs has varying degrees of negative impact on obesity, cardiovascular metabolism, skeletal muscle development, and cognitive, and psychological disorders in children and adolescents. (2) Regular physical activity could effectively prevent, offset, or improve the harm of SB to the physical and mental health of children and adolescents, mainly by reducing the incidence of obesity, and cardiovascular and metabolic risks, promoting skeletal muscle development, and improving cognitive function and mental health. (3) The mechanism of physical activity to prevent or ameliorate the harm of SB was relatively complex, mainly involving the inhibition or activation of neurobiomolecules, the improvement of blood and cell metabolic factors, and the enhancement of brain functional connectivity. Conclusions Children and adolescents should avoid excessive SB, and through a variety of moderate to vigorous physical activity (MVPA) to replace or intermittent SB, which could effectively prevent or improve the harm of SB to physical and mental health.